PERANAN PENERBIT DALAM PENGEMBANGAN SASTRA DI RIAU - Sri Sabakti (Madah: Jurnal Bahasa dan Sastra, 2012)
The development of intelectual literary of authorship in Riau has shown the increasing from time to time. The increasing number of writers is in line with the increasing number of local publishers. Based on the information received, almost all of the local publishers published literary books. The first question is how the dynamics of publisher in Riau are. The second question is what the role of the publishers in the development of sastra in Riau are. Both of the questions are interested to be researched by using the sociological theory of literary, Escarpit. The result of the research showed that most of the publishers in Riau were established in order to motivate the local writers (Riau) in writing and to participate in the development of the repertoire and treasury of the literature books, especially in Riau Province. It can bee seen that the role of local publishers in the literary development is wide enough, especially in the documentation of literary books, the orbitting of Riau writers and as the means of supporting The Vision of Riau 2020 especially in culture (literary).